Assessing the reversed gender gap in the Swedish crime survey: reasons why young women report higher victimization rates than young men during the period 2009 to 2016 - Hagerlid, Mika (Crime & delinquency, 2024)
Self-reported victimization among young women in the Swedish Crime Survey increased during the early- to mid-2010s, resulting in a gender gap, with young women reporting 10% to 15% higher victimization rates than young men. In this study, we use multi-group confirmatory factor analysis to assess whether the increase in victimization rates is due to declines in measurement equivalence across different cohorts of young women during the period 2009 to 2016. The results show cohort differences in how young women interpret the victimization items in the Swedish Crime Survey, especially with regard to the item about sexual victimization. The results show that the increasing victimization rates are likely the result of changes in perceptions about sexual offences, rather than an actual increase.